Stylistic features of black cinema in America (Al-Academy, 2026)
Branching out from the fictional film are many cinematic films that deliberately address topics in an aesthetic and expressive manner to convey the copyright content to the recipient. Therefore, all cinematic films began with the existence of the art of cinematography, and black cinema took on the specificity that partly attempts to be fictional, including reflecting their identity. And the presence of that alternating current. Among other currents, the researcher tries to shed light on the features that distinguish this cinema from the rest of the cinema.